Microcystins Exposure and the Risk of Metabolic Syndrome: A Cross-Sectional Study in Central China - Shuidong Feng; Yuke Zeng; Fengmei Song; Minxue Shen; Fei Yang (Toxins)
A growing body of evidence indicates that microcystins (MCs) exposure may cause metabolic diseases. However, studies exploring the effects of MCs exposure on the risk of metabolic syndrome (MetS) in humans are currently lacking, and the underlying mechanisms remain unclear. Here, we conducted a cross-sectional study in central China to explore the effect of serum MCs on MetS, and assessed the mediation effects of the inflammation biomarker, white blood cell (WBC) level, in this relationship. The relationships among MCs and WBC level and risk of MetS were assessed using binary logistic and linear regression. Mediation analysis was used to explore possible mechanisms underlying those associations by employing R software (version 4.3.1). Compared to the lowest quartile of MCs, the highest quartile had an increased risk of MetS (odds ratio [OR] = 2.10, 95% confidence interval [CI]: 1.19, 3.70), with a dose–response relationship (p for trend < 0.05). WBCs mediated 11.14% of the association between serum MCs and triglyceride (TG) levels, but did not mediate the association of MCs exposure with MetS. This study firstly reveals that MCs exposure is an independent risk factor for MetS in a dose–response manner, and suggests that WBC level could partially mediate the association of MCs exposure with TG levels.